(untitled) (Researcher CAB: A Journal for Research and Development, 2024)
Customer satisfaction is essential for businesses to encourage them to share positive responses in buying products. It stands as a crucial factor in determining long-term success of any organization reflecting the extent to which their offerings satisfy customer expectations. The economic progress and business success rely on customer satisfaction affected by the empathy, assurance, responsiveness, tangibility, reliability etc. especially in banking sector. Therefore, this study examines how bank customers perceive service quality and impact on their satisfaction. It utilizes a descriptive and causality research design to explore the relationship between drivers of service quality and customer satisfaction based on primary survey data from Kathmandu valley. This paper concludes reliability, assurance, tangibility, empathy, and responsiveness as service quality drivers play a significant role in shaping customer satisfaction within the banking sector. Notably, tangibility, assurance, and empathy stand out as key influential drivers in determining customer satisfaction level in commercial banks within Kathmandu valley. The significance of this research lies in its relevance to policymakers in the banking sector, urging them to develop and execute diverse bank policies aiming to enhance customer satisfaction, thereby fostering the business and economic success of commercial banks in Nepal.